THE EFFECT OF CERTIFICATION ASSESSMENT TO TEACHER COMPETENCE AND ITS IMPLICATIONS ON STUDENT LEARNING ACHIEVEMENT - Nelis Supriati; Budi Hendriyana; Sukma Murni (IKIP Siliwangi, 2018)
Certification means to improve the quality of teacher competence. Certification allowances still raise questions about low teacher competency and student learning achievement. Based on this, a study was conducted on the effect of certification (x) benefits on teacher competency (y) and their implications for student learning achievement (z). The research aims: 1) Effect of certification benefits on teacher competence. 2) Effect of teacher competence on student learning achievement. 3) Efforts need to be made to improve teacher competency and student learning achievement. Research uses descriptive methods with quantitative approache. The sampling technique used is saturated sampling technique. The sample consisted of 33 teachers. Samples were selected with nonprobability sampling technique. Data collection using questionnaires, interviews, and student test results. Validity test using product moment formula, and reliability testing using the alpha coefficient formula. Data analysis techniques used product moment correlation, path analysis and t test with SPSS version 21. Research results: 1) Teacher certification allowance (x) has a positive effect on teacher competence (y). This is evidenced by the results of the correlation coefficient (r) of 0.586 and the strength of the influence of 0.443. 2) Teacher competency (y) has a positive effect on student learning achievement (z). This is proven by the results of the correlation coefficient (r) is 0.708 and the power of influence is 0.501